Profil Kondisi Fisik Pemain Sepakbola Wanita Candra Kirana - Muhammad Akbar Husein Allsabah; Weda Weda; Irwan Setiawan; Aulia Safrotun Nimah (STKIP Muhammadiyah Kuningan, 2019)
The purpose of this study was to determine the profile of physical conditions as monitoring conditions before participating in the 2019 Pertiwi competition in order to get proud results. This type of research is non-experimental with analysis techniques of collecting data using survey methods and test techniques. The research approach uses quantitative. The subjects used in this study were female soccer players who were members of the Candra kirana club in Kediri Regency, aged 18-20 years, totaling 20 players. The data obtained from each test item is crude data and is converted into t-score values ​​with the next t-score formula. The data is interpreted, namely by categorizing the data into 5 categories. Based on the results of the research that has been found, it can be concluded that the profile of the physical condition of the Candra Kirana players in Kediri Regency is included in a sufficient category with a percentage of 45%